Critical conductance of two-dimensional electron gas in silicon-on-insulator metal-oxide-semiconductor field-effect transistor. (23rd September 2021) - Razanoelina, Manjakavahoaka; Hori, Masahiro; Fujiwara, Akira; Ono, Yukinori
Abstract: Conductance of thin (18 nm) silicon-on-insulator (SOI) metal-oxide-semiconductor field-effect transistor is investigated from the viewpoint of metal insulator transition (MIT). Conductance characteristics taken in the parameter space defined by the front- and back-gate voltages in a temperature range on the order of 10 K reveal that the critical conductance G C, separating the metallic and insulating states, varies with the gate voltages. In particular, it is found that G C of the double (front and back) channel mode is not a simple sum of G C for the two single (front or back) channel modes, but becomes lower than the sum. This is a unique feature of the MIT in thin SOIs, and strongly suggests that modulation of the electron wavefunction due to the vertical confinement affects the MIT properties in thin SOIs.